ANALISIS JENIS AGROINDUSTRI DAN KELAYAKAN PENDIRIAN AGROINDUSTRI BERBASIS IKAN DI KABUPATEN TULANG BAWANG - Moralita Tauhid (Jurnal Teknologi & Industri Hasil Pertanian, 2017)
This study aims to get the kind of fish-based agroindustry potential to be developed in Tulang Bawang, determine the location of fish-based agroindustry and the feasibility of establishing fish-based agroindustry. This research was determination of agroindustry based potential comodity by using Analitycal Hierarchy Process (AHP) methode and the feasibility of establishing fish-based agroindustry selected from financial aspect and sensitivity analysis. The result showed nugget agroindustries will be developed. Bandeng nugget agroindustry meet the eligibility criteria that NPV positive value of Rp. 1.275.965.898.978, the IRR is greater than the discount factor of 12,75%, ie 55%, the value of B/C ratio is greater than 1 is 1,3 and the payback period of 7 years and 9 months, and based on sensitivity analysis to the increase of raw material is obtained that the feasibility of agroindustry maximum on the increase in raw materials of 12% per year.